The outcomes of Latin consonant groups with lateral consonant in Italian dialects - Kovačić, Vinko (2014)
The Latin consonant groups that consist of a consonant followed by the lateral consonant /l/ have different outcomes in the Italian dialects. In this paper are analysed, compared and described the cases of that phenomenon in the Italo-Romance dialectal system. There are five consonant groups of this kind that exist in Latin : four groups with a plosive consonant (BL, CL, GL, PL) , and one with a spirant (FL). The focus is on the consonant groups in the initial position of a word, but there will also be mentioned those in the internal position since they don't have always the same outcomes.
ENG